EOCENE AND OLIGO‐MIOCENE SOURCE ROCKS IN THE RIONI AND KURA BASINS OF GEORGIA: DEPOSITIONAL ENVIRONMENT AND PETROLEUM POTENTIAL. (15th June 2018) - Pupp, M.; Bechtel, A.; Ćorić, S.; Gratzer, R.; Rustamov, J.; Sachsenhofer, R. F.
Abstract : For over a century, oil has been produced in Georgia from oilfields located in the foreland basins between the Greater and Lesser Caucasus foldbelts. To date, little information on the associated source rocks has been available. In this context, this paper presents a study of 380 samples of Eocene (Kuma Formation) and Oligocene to Lower Miocene (Maikop Group) source rocks from three outcrop sections in the Rioni and Kura Basins. The Kuma Formation in the Rioni Basin is composed of fully‐marine marls and is about 40 m thick. At the Martivili and Khobi sections, the formation is thermally immature and has an average TOC of 3.2 wt%. The hydrogen indices (HI) of 300–600 mg HC/g TOC indicate that the organic matter is oil‐prone Type II kerogen. The oil generation potential is between 1.0 and 2.4 t HC/m 2, and the Kuma Formation is therefore interpreted as a prolific source rock. The Maikop Group in the Rioni Basin was studied at the Martvili section, where it is thermally immature. The Oligocene succession is divided by calcareous shales deposited during the Solenovian Event (at the onset of nannoplankton zone NP23) into Pshekhian and Solenovian‐to‐Kalmykian intervals. The Pshekhian interval (NP21‐22) is over 60 m thick and comprises a marly lower part and a shale‐rich upper part, and contains high quantities (average 2.7 wt% TOC) of Type II‐III kerogen (average HI: 278 mg HC/g TOC). The overlying largely carbonate‐free shale succession, 424 m thick, is less organic matter ‐rich (∼2.0 %TOC) and contains dominantly Type III kerogen (average HI: 140 mg HC/g TOC). In total, the Maikop Group has a generation potential of about 4 t HC/m 2, a value which is higher than in most other sub‐basins in the Eastern Paratethys. Because the Rioni Basin continues westwards into the Black Sea, these results are relevant for future exploration in the eastern part of the Black Sea Basin. The Maikop Group in the western Kura Basin in the Tbilisi area is over 3500 m thick and includes numerous sandstone beds. Because of the great thickness of the Maikop Group and the presence of about 3 km of overburden, which was removed during Miocene to Recent unroofing, potential source rocks in the Eocene to Lower Oligocene succession have reached oil window maturities but their hydrocarbon potential is low.